2021
DOI: 10.3389/fcimb.2021.726282
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Risk Factors for Carbapenem-Resistant Klebsiella pneumoniae Infection and Its Effect on the Outcome of Early Infection After Kidney Transplantation

Abstract: BackgroundInfections remain a major cause of morbidity and mortality in kidney transplant (KT) recipients. This study was performed to identify the overall prevalence of early infections, prevalence of carbapenem-resistant Klebsiella pneumoniae (CRKP) infection after KT, one-year postoperative mortality in patients with early infections and risk factors for CRKP infections.MethodsWe conducted a retrospective study of all patients who received KT in our hospital between January 2017 and December 2019. We evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…A previous study reported that CRKP appeared to be an independent risk factor for 1-year postoperative mortality in patients after kidney transplantation ( 44 ). Additionally, some studies demonstrated that CRKP infection was one of the independent risk factors for death from Kp bloodstream infection ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that CRKP appeared to be an independent risk factor for 1-year postoperative mortality in patients after kidney transplantation ( 44 ). Additionally, some studies demonstrated that CRKP infection was one of the independent risk factors for death from Kp bloodstream infection ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that CRKP isolation is associated with high in-hospital mortality, which is similar to those reported in previous publications. 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…Our survey showed that twelve (63.2%) cases were dead in 19 CRKP-infected recipients. In kidney transplant recipients, the length of MV (>48h) was an independent risk factor for recipient infection death and CRKP infection ( Zhang et al., 2021 ). Some case-control studies also showed that longer MV length, longer ICU length, and elder age were independent risk factors for CRKP infection mortality ( Jiao et al., 2015 ; Akgul et al., 2016 ; Chen et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The multi-drug-resistant (MDR) bacterial pathogens emerged with the clinical application of advanced antibiotics ( Verma et al., 2022 ), such as Carbapenem-resistant Klebsiella pneumoniae (CRKP). Multiple studies have shown that the infection of MDR pathogens is the primary factor affecting the early survival rate of solid organ transplantation recipients ( Li et al., 2014 ; Zhang et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%